Evaluation of root canal obturation using gas permeability method - Matović Ivan; Teodorović Nevenka; Marjanović Marina (Serbian Medical Society - Dental Section, Belgrade, 2013)
Introduction. Prognosis of root canal treatment is highly dependent on the quality of endodontic space obturation. The main task of successful root canal treatment is to achieve adequate reparation processes in the apical periodontium. The aim of this study was to evaluate the quality of root canal obturation using the method of gas (argon) penetration through three different endodontic materials. Material and Methods. Thirty recently extracted human single-rooted teeth after root canal instrumentation were divided into three identical groups and obturated with three different endodontic materials: group I - GuttaFlow (RSA, Germany), group II - AH Plus (DeTray, Germany), group III - Acroseal (Septodont, France). The quality of root canal obturation was evaluated using the method of gas permeability. Results. The best results were obtained with GuttaFlow. The average penetration rate of argon was 186.7 seconds. Slightly higher gas porosity had AH Plus, 179.9 seconds, while the highest gas permeability was observed after the application of Acroseal, 178.5 seconds. However, there was no statistically significant difference in gas penetration among these endodontic materials (p>0.05). Conclusion. All three endodontic materials showed gas permeability in a given time interval. The best quality of obturation was achieved with GuttaFlow, while the lowest quality was obtained with Acroseal.